A Case of Limited Vision: Jabotinsky on Canada and the United States - Brown, Michael (Canadian Jewish Studies / Études juives canadiennes, 1993)
Canadian Jewish communities were quicker than their American counterparts to support the Zionist cause. But during the inter-war period, when changing circumstances in Europe forced Zionist leaders to shift their search for potential immigration and financial support from the Old World to the New, the Canadians' efforts were largely ignored. Apathy, even resistance, characterized much of the American Jewish community's response to the Zionist leadership. Still, the United States remained the preoccupation of leaders such as Vladimir Jabotinsky, founder of what would become the right-wing Likud party.